Pest That Affect Human Health, Scabies - Kramer, Wayne L.; Mock, Donald E. (My University, 1996)
This publication describes Scabies and how to get rid of them.
MF2094_1996_09
Keywords: MF2094; Health and Safety; Home and Family; MF